2014
DOI: 10.2478/s13545-014-0154-7
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of potentially human pathogenic bacteria in the seawater and in the sand of the recreational coastal beach in the southern Baltic Sea

Abstract: The occurrence and the distribution of potentially human pathogenic bacteria such as Aeromonas, Pseudomonas aeruoginosa, Staphylococcus and Vibrio-like organisms in the sand and the adjacent seawater of the recreational coastal beach were studied. The highest mean number among these four studied groups of bacteria was represented by Aeromonas-like organisms and the lowest one by Staphylococcus-like organisms. Dry sand was inhabited by the highest number of all studied potentially pathogenic bacteria. Within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…This bacterial range is found to be lower as compared to the data from the present study. A study by Mudryk et al (2014) from the coastal Baltic Sea showed the counts of Aeromonas to be higher as compared to Pseudomonas and E. coli, whereas in the present study the highest numbers were seen for Pseudomonas counts. When studies from the Indian coast are concerned regarding indicator and pathogenic bacteria, the East Coast (off Chennai) showed a higher abundance of total viable counts, and total coliforms as compared to the West Coast of India (off Kerala) (Sudhanandh et al, 2012;Vignesh et al, 2012).…”
Section: Spatial Distribution Of Bacterial Numberscontrasting
confidence: 80%
“…This bacterial range is found to be lower as compared to the data from the present study. A study by Mudryk et al (2014) from the coastal Baltic Sea showed the counts of Aeromonas to be higher as compared to Pseudomonas and E. coli, whereas in the present study the highest numbers were seen for Pseudomonas counts. When studies from the Indian coast are concerned regarding indicator and pathogenic bacteria, the East Coast (off Chennai) showed a higher abundance of total viable counts, and total coliforms as compared to the West Coast of India (off Kerala) (Sudhanandh et al, 2012;Vignesh et al, 2012).…”
Section: Spatial Distribution Of Bacterial Numberscontrasting
confidence: 80%
“…This means that Aeromonas are able to detoxicate those pharmaceutical organic compounds and according to Radu et al (2003) the high level of multiple resistance may arise from selective pressure due to the indiscriminate use of antibiotics. Adaptive responses of bacterial communities to several antibiotics noted in the present study may presumably re ect the history of antibiotics application in the studied ponds (Mudryk et al 2014). Most classes of antibiotics that are approved for human and animal use are introduced into water basins ( Ecconomou and Gouisa 2015; Kim et al 2015).…”
Section: Discussionmentioning
confidence: 80%
“…Those inhabiting the in ow region were resistant to nearly all tested antibiotics compared to bacteria inhabiting the out ow region of the studied water bodies. Also Mudryk et al (2014) and Cisar et al (2014) in their research documented that bacteria that differed in antibiotic resistance inhabited different parts of the water basins.…”
Section: Discussionmentioning
confidence: 99%
“…These were then shaken for 1 minute to dislodge any bacteria present. 16 With the aid of inoculating loops, the inocula were transferred unto petri dishes containing the respective media. Oxoid UTI Chromogenic Agar (clear) and Uriselect 4 were used for presumptive identification of bacteria such as E. coli, Enterococcus faecalis , Pseudomonas aeruginosa , and Staphylococcus aureus .…”
Section: Methodsmentioning
confidence: 99%